2010
DOI: 10.1002/bjs.6999
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of intravenous soybean oil alone versus soybean oil plus fish oil emulsion after gastrointestinal cancer surgery

Abstract: Fish oil emulsion-supplemented parenteral nutrition significantly reduced SIRS and length of hospital stay. These clinical benefits may be related to normalization of cellular immune functions and modulation of the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 21 publications
(24 reference statements)
1
70
2
4
Order By: Relevance
“…Among 17 studies, 11 studies [2,11,12,23,24,26,27,29,30,32,33] used an adequate approach to sequence generation using computer generated random numbers or random-number tables. The adequacy of randomization was unclear in the remaining 6 studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Among 17 studies, 11 studies [2,11,12,23,24,26,27,29,30,32,33] used an adequate approach to sequence generation using computer generated random numbers or random-number tables. The adequacy of randomization was unclear in the remaining 6 studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Figure 1 shows the process for identifying potentially eligible studies and exclusion criteria. After elaborative screening, 34 articles were assessed by full text and 17 studies with 753 patients [2,[10][11][12]15,16,[23][24][25][26][27][28][29][30][31][32][33] were included for the review. However, three publications [2,24,30,31,33] are same study that reported different outcomes.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Isto mostra que os efeitos dos AG podem ser obtidos em pacientes que não conseguem se alimentar normalmente e precisam do suporte da alimentação parenteral. 22,[41][42][43] Barbalho SM, Bechara MD, Quesada KR, Goulart RA. Papel dos ácidos graxos ômega 3 na resolução dos processos inflamatórios…”
Section: Introdução Introdução Introdução Introduçãounclassified